ANALYTICAL AND NUMERICAL STUDY OF DAM BREAK PHENOMENA USING SHALLOW WATER EQUATIONS - Widijanto, Shannen
Dam is a construction built by the government mainly to prevent flood. Dam break may cause disasters that gives negative impacts on the surrounding area. The kinetic energy generated by the water flow could affect how big the damage occurs. This final project discusses about dam break, either dry bed or wet bed dam break. Shallow Water Equations (SWE) is used as the mathematical model and the analytical study is carried out by solving Riemann Problem for SWE. Momentum Conservative Scheme (MCS) on a staggered grid is implemented in numerical simulation. The results of numerical simulations are in agreement with the analytical solutions for dry bed and wet bed. This final project also discusses dam break problem using 2D SWE model. MCS is also applied in 2D SWE model to simulate dam break that connects to a channel. This numerical model is used to calculate kinetic energy generated by the water flow when dam breaks. In this case, the kinetic energy is calculated when water flow hits the hard wall for various length and width of the channel. Based on the simulation results, the difference in the width of the channel causes a significant change in the kinetic energy produced while the difference in the length of the channel does not really affect the kinetic energy produced.